MENELISIK DAMPAK PERKEBUNAN KELAPA SAWIT BAGI HUTAN ADAT, HAK ULAYAT, DAN VISI EKOLOGIS MASYARAKAT HUKUM ADAT DI KALIMANTAN BARAT - Samho, Bartolomeus; Slamet Purwadi, Yohanes (Veritas et Justitia, 2023)
According to the result of a research conducted in 2016 entitled "Changes in the Mindset of Dayak Indigenous Peoples in Sanggau Regency towards Customary Forests as a Result of Palm Oil Plantations", this article aims to describe the impact of oil palm plantations on indigenous forests, customary rights, and the ecological vision of Adat communities in West Kalimantan. The research method used is a qualitative method with a phenomenological approach. The findings of this research indicate that economic benefits obtained from oil palm plantations are not proportional with the ecological and social losses resulting from the impacts, both directly and indirectly. It is also found that Adat communities living around oil palm plantations often face the threat of horizontal conflicts due to competition over cultivated land and ecological threats in the form of floods and landslides. The findings within thisis useful to strengthen the understanding of the importance and necessity of developing oil palm plantations with due regard to the local wisdom and constructive ecological vision to maintain the existence of indigenous forests as customary rights. Therefore, land clearing for oil palm plantations must pay attention to local wisdom, preserving nature so that the sustainability of ecosystems and communities is guaranteed.